2011
DOI: 10.3109/07388551.2011.615297
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives of gibberellic acid production: a review

Abstract: The gibberellins (GAs) are an important group of hormones which exert various effects on promoter and regulator of plant growth. Gibberellic acid (GA(3)) is a natural plant hormone, with great economical and industrial importance. It affects stem elongation, germination, elimination of dormancy, flowering, sex expression, enzyme induction and leaf and fruit senescence. Despite its diverse applications, the use of GA(3) is limited due to its high production costs. The industrial process currently used for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 126 publications
1
51
0
Order By: Relevance
“…Gibberellic acid ( G , Figure 2) is a plant hormone isolated from Gibberella fujikuroi 22 and produced industrially 23 on the ton scale. Gibberellic acid contains a tetracyclic diterpene core with a fused lactone, two allylic alcohols, an exocyclic olefin, and a carboxylic acid, enabling selective and independent functionalization of each ring of the core structure via a variety of ring system distortion reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Gibberellic acid ( G , Figure 2) is a plant hormone isolated from Gibberella fujikuroi 22 and produced industrially 23 on the ton scale. Gibberellic acid contains a tetracyclic diterpene core with a fused lactone, two allylic alcohols, an exocyclic olefin, and a carboxylic acid, enabling selective and independent functionalization of each ring of the core structure via a variety of ring system distortion reactions.…”
Section: Resultsmentioning
confidence: 99%
“…GAs comprises a group of growth hormones that control diverse processes, such as cell elongation, reproductive growth and senescence [54]. Previous reports showed that GAs are inhibitors of leaf senescence [55,56].…”
Section: Resultsmentioning
confidence: 99%
“…GA is a pentacyclic diterpene which influences the (1) cell elongation, (2) dormancy, (3) seed germination, (4) senescence, and (5) tolerance against environmental stresses (Rodrigues et al 2011). Actually, no data on the action of exogenously applying GA to plants neither the effect of O 3 on GA biosynthesis and signaling pathway are found in literature despite its prominent role in the mitigation of environmental stresses.…”
Section: Gibberellins (Gas) Auxins (Iaas) and Cytokinins (Cks)mentioning
confidence: 95%